Сценарный метод как доминантный при формировании лингвокультурологической компетенции иностранных учащихся - Нагайцева, Нина Ивановна; Виктор, Ольга Михайловна (Харківський національний університет радіоелектроніки, 2019)
Статья посвящена сценарному методу как превалирующему в совокупности методов преподавания русского языка как иностранного. На примере опыта его использования на факультете международного образования НТУ "ХПИ" показано, что данный метод активно влияет на формирование лингвокультурологической компетенции иностранных учащихся.

The article "A scenario method used as the dominant one in the formation of linguoculturological competence of foreign students" deals with the description and analysis of the value of a scenario method which is used in extracurricular ac-tivities at the Department of International Education of NTU KhPI. This method is prevailing among the other methods of Russian language teaching as a foreign language because it influences the formation of a language personality through culture. A scenario method is he most suitable in the preparation of theatrical productions at the Department of International Education with the participation of foreign students. These productions are as follows: musical performances based on fairytales such as "Teremok", "Repka", "Mukha-Tsokotukha", mini performances based on the poems by S. Marshak, fables by I. Krylov. The preparation of any performance requires a lot of mental, intellectual and physical efforts, both students and teachers. But it is rewarded by the output results: the monolithic creative team is formed, warm relationships among students and teachers-directors are establisheёd, the foundations for "penetration" of cultures and mentalities of students form different countries and regions of the world are laid. Moreover, the personalities of "actors" are changed making them more liberated not only on the scene but also in life. The students develop themselves, raise the level of their self-esteem, boost their emotional and creative thinking. Thanks to international communication in Russian language the fear of foreign (Russian) language goes away and notorious "language barrier" is destroyed. Furthermore, the language, which students study, is improved in phonetics, grammar structures, vocabulary and so on. As a result, both performers and audience get interested in theater and the life at the Department of International Education be-comes diverse, vivid and bright. It can be concluded that a scenario method as a fundamental method of educational activity brings matchless outcomes.
A scenario method used as the dominant one in the formation of linguoculturological competence of foreign students
Keywords: сценарный метод; культура; язык; творчество; лингвокультурологическая компетенция; спектакль; сценарий; текст; роль; проникновение культур